Effect of processing on the alkaloids in Aconitum tubers by HPLC-TOF/MS - Min Liu; Yan Cao; Diya Lv; Wen Zhang; Zhenyu Zhu; Hai Zhang; Yifeng Chai (Elsevier, 2017)
According to the Chinese Pharmacopoeia 2015, only processed Aconitum tubers can be clinically applied, and the effect of processing is unclear. This research aimed to explore the effect of processing on cardiac efficacy of alkaloids in Aconitum tubers. First, the chemical ingredients in unprocessed and processed Aconitum tubers were identified and compared by using high performance liquid chromatography time-of-flight mass spectrometry (HPLC-TOF/MS) and multivariate pattern recognition methods. Then the representative alkaloids in Aconitum tubers, aconitine, benzoylaconine, and aconine, which belong to diester-diterpenoid alkaloids, monoester-diterpenoid alkaloids, and amine-diterpenoid alkaloids, respectively, were selected for further validation of attenuated mechanism. Subsequent pharmacological experiments with aconitine, benzoylaconine, and aconine in SD rats were used for validate the effect of processing on cardiac functions. After processing the Aconitum tubers, it was found that the contents of diester-diterpenoid alkaloids were reduced, and those of monoester-diterpenoid alkaloids and amine-diterpenoid alkaloids were increased, suggesting that diester-diterpenoid alkaloids were transformed into monoester-diterpenoid alkaloids and amine-diterpenoid alkaloids. Through further decocting the aconitine in boiling water, it was confirmed that the three alkaloids could be progressively transformed. Pharmacological experiments with aconitine, benzoylaconine, and aconine in SD rats showed that aconitine at a dose of 0.01 mg/kg and aconine at a dose of 10 mg/kg enhanced the cardiac function, while benzoylaconine at a dose of 2 mg/kg weakened the cardiac function. The effect of processing is attributed to the transformation of the most toxic diester-diterpenoid alkaloids into less toxic monoester-diterpenoid alkaloids and amine-diterpenoid alkaloids.